Prediksi Harga Saham PT Bank Danamon Indonesia Tbk (BDMN) Menggunakan Metode Autoregressive Integrated Moving Average (ARIMA) - Nurul Aini; Dwi Solehah; Lidwina Ritan; Tiara Ilham (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2026)
This study aims to predict the daily closing price of BDMN shares (PT Bank Danamon Indonesia Tbk) using the Autoregressive Integrated Moving Average (ARIMA) model. The dataset consists of 789 daily observations from January 2023 to May 2026, sourced from Investing.com and Yahoo Finance. Fundamentally, BDMN demonstrates a sound condition: Net Interest Margin (NIM) is maintained above 8%, Non-Performing Loan (NPL) is below 3%, Return on Equity (ROE) ranges between 10–14%, and Capital Adequacy Ratio (CAR) stands at 27.5%, well above the 8% minimum threshold, under majority ownership of MUFG Bank. Analysis was conducted using RStudio with the forecast and tseries packages. ARIMA(3,1,2) was selected as the best model with AIC = 8,467.68. Accuracy metrics are: RMSE = 51.66, MAE = 28.74, and MAPE = 1.04%, classified as highly accurate (well below the 10% threshold). The Ljung-Box test confirms residuals exhibit white noise behavior (p-value = 0.3075). The 20-period forecast places BDMN stock prices in the range of Rp 4,100–4,280.